Overcoming dietary complexity in type 2 diabetes: influencing factors and coping strategies - Yingying Tang; Dongmei Yang (European Journal of Medical Research)
Abstract Background Adherence to dietary guidelines is a fundamental aspect of diabetes management; however, it poses a significant challenge for patients with diabetes. Our research aims to assess the level of dietary compliance among individuals with type 2 diabetes (T2DM) and to identify the factors that influence their adherence to dietary advice. Methods This study was a cross-sectional survey. The patients with T2DM undergoing treatment at our hospital from March, 2023, to June, 2024 were included. Compliance with dietary recommendations was assessed using the validated dietary compliance scale for type 2 diabetes mellitus patients (DCS-T2DM). Spearman correlation and logistic regression analyses were conducted to evaluate the factors influencing dietary compliance in patients with T2DM. Results A total of 308 T2DM patients were included in our study. The results revealed that 46.10% of the participants had suboptimal dietary compliance. There were significant correlations between dietary compliance and several demographic and clinical factors, including age (r = 0.501), gender (r = 0.447), education level (r = 0.610), average monthly household per capita income (r = 0.627), and the duration, since T2DM diagnosis (r = 0.552), all of which were statistically significant (p < 0.05). Logistic regression identified age (OR = 1.705, 95%CI 1.262 ~ 1.987), gender (OR = 2.401, 95%CI 1.909 ~ 3.134), education level (OR = 3.083, 95%CI 2.434 ~ 3.957), average monthly household per capita income (OR = 3.721, 95%CI 2.553 ~ 4.405), and the time since T2DM diagnosis (OR = 2.470, 95%CI 1.755 ~ 3.262) as significant predictors of dietary compliance. Conclusions 46.10% of patients with T2DM exhibited suboptimal dietary adherence, with age, gender, education, income, and diabetes duration significantly predicting compliance. It is imperative for healthcare providers to devise individualized intervention strategies that incorporate these pivotal factors to enhance dietary adherence in patients with T2DM.